2013
DOI: 10.5455/aim.2013.21.205-207
|View full text |Cite
|
Sign up to set email alerts
|

P300 Wave Changes in Patients with Multiple Sclerosis

Abstract: Introduction:In patients with multiple sclerosis among other symptoms occur cognitive dysfunctions, which can be shown by P300 wave changes.Goal:The aim of this study was to demonstrate that patients with multiple sclerosis have reduced amplitude and prolonged latency, longer than 300 ± 10 ms.Methods:The study included group of patients with multiple sclerosis and control group. After reviewing the medical records both groups of 14 participants were subjected to the same testing procedures auditory cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
0
9
0
3
Order By: Relevance
“…The P300 event-related potential is an objective electrophysiologic examination that reflects brain cognition function [ 25 , 26 ]. Related research has shown that patients with mild cognitive impairment exhibit changes in P300 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The P300 event-related potential is an objective electrophysiologic examination that reflects brain cognition function [ 25 , 26 ]. Related research has shown that patients with mild cognitive impairment exhibit changes in P300 [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing interest in radiological and neurophysiological correlates of cognitive dysfunction in MS. Reports on other ERPs such as P300 or mismatch negativity in MS patients can be found in the literature, 25 , 26 , 27 but there has been a paucity of research on CNV in this patient group. 28 To the best of our knowledge, this is the first study to examine the association between CNV and neuropsychological functioning in MS patients, and the first to examine CNV differences between RRMS and SPMS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Латентный период Р300 был достоверно увеличен только в группе детей с РС и в среднем на 22 мс превышал норму (p <0,01). Замедление скорости когнитивных процессов у больных РС в виде увеличения латентного периода Р300 в нашем исследовании подтверждается данными других исследований с использованием КВП на слуховой стимул, что объясняется процессом демиелинизации [20]. B. S. Giesser и соавт.…”
Section: результатыunclassified